2010
DOI: 10.3390/toxins2061554
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant Adaptation of a Blood Coagulation Prothrombinase-like Enzyme Complex in Australian Elapid Venom

Abstract: The macromolecular enzyme complex prothrombinase serves an indispensable role in blood coagulation as it catalyzes the conversion of prothrombin to thrombin, a key regulatory enzyme in the formation of a blood clot. Interestingly, a virtually identical enzyme complex is found in the venom of some Australian elapid snakes, which is composed of a cofactor factor Va-component and a serine protease factor Xa-like subunit. This review will provide an overview of the identification and characterization of the venom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Venom FV from Pseudonaja textilis (ptex-FV) has a B-domain of just 46 residues that lacks the BR but contains a region similar to AR. Consistent with the importance of an intact PRR in keeping FV inactive, we have shown that ptex-FV is constitutively active and does not require processing/removal of its B-domain (42,43).…”
Section: Contribution Of Additional B-domain Sequences To Maintainingsupporting
confidence: 50%
“…Venom FV from Pseudonaja textilis (ptex-FV) has a B-domain of just 46 residues that lacks the BR but contains a region similar to AR. Consistent with the importance of an intact PRR in keeping FV inactive, we have shown that ptex-FV is constitutively active and does not require processing/removal of its B-domain (42,43).…”
Section: Contribution Of Additional B-domain Sequences To Maintainingsupporting
confidence: 50%
“…The venom coagulation factors VF5 a and VF10 a are present in large amounts in some Australian Elapidae venom such as Oxyuranus microlepidotus, Oxyuranus scutellatus and Pseudonaja textilis (Bos and Camire, 2010;Masci et al, 1988). In P. textilis venom, VF5 a and VF10 a form the prothrombinase complex named Pseutarin-C (Kini et al, 2001), with similar characteristics to the blood plasma prothrombinase complex, essential for blood clot formation by converting prothrombin into thrombin (Mann et al, 1990;Rao and Kini, 2002).…”
Section: Prothrombinase Complex: Coagulations Factors Va and Xamentioning
confidence: 97%
“…Most MAHA cases were observed following taipan ( Oxyuranus species, 26% MAHA cases) and brown snake ( Pseudonaja species, 14% MAHA cases) envenoming, while bites from Notechis and Hoplocephalus species each led to MAHA in 7% of envenomed individuals. Interestingly, this correlates with the venom composition of these snakes, with both Oxyuranus and Pseudonaja venom comprising factor Xa‐Va‐like prothrombin activators, while a factor Xa‐like protease is found in the venom of Notechis and Hoplocephalus snakes . Also, the onset of VICC appears to proceed more rapidly following envenoming by Pseudonaja snake bites relative to those of Notechis snakes, and MAHA only seems to occur following VICC‐associated snakebites .…”
mentioning
confidence: 97%
“…This study clarified that the most commonly observed clinical envenoming phenotype in Australia is venom‐induced consumptive coagulopathy (VICC), an unbridled activation and consumption of the coagulation system. This is due to the venom composition of the snakes that are most commonly involved in these envenomings; Pseudonaja species contain procoagulant factor Xa‐Va‐like and Notechis species factor Xa‐like enzymes . Once injected into the blood stream of the prey, the Notechis factor Xa‐like protease interacts with prey factor V(a), and the circulating venom factor Xa‐Va‐like enzymes are capable of converting prothrombin of the prey into thrombin .…”
mentioning
confidence: 99%
See 1 more Smart Citation